1991
DOI: 10.1016/0920-5632(91)90880-n
|View full text |Cite
|
Sign up to set email alerts
|

Regularity properties and pathologies of position-space renormalization-group transformations

Abstract: We reconsider the conceptual foundations of the renormalization-group (RG) formalism, and prove some rigorous theorems on the regularity properties and possible pathologies of the RG map. Regarding regularity, we show that the RG map, de ned on a suitable space of interactions (= formal Hamiltonians), is always single-valued and Lipschitz continuous on its domain of de nition. This rules out a recently proposed scenario for the RG description of rst-order phase transitions. On the pathological side, we make ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 174 publications
(374 reference statements)
0
16
0
Order By: Relevance
“…Historically they were observed first in the context of position-space renormalization group transformation and termed as so-called RG pathologies [11]. Later more and more examples were discovered [2,4,8,19,24] which showed that the application of many maps applied to an infinite-volume Gibbs measure may result in similar "pathologies", meaning that the image measure is not a Gibbs measure anymore. When such a phenomenon appears it means that conditional probabilities of the image system will acquire long-range dependencies, at least for some non-removable configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Historically they were observed first in the context of position-space renormalization group transformation and termed as so-called RG pathologies [11]. Later more and more examples were discovered [2,4,8,19,24] which showed that the application of many maps applied to an infinite-volume Gibbs measure may result in similar "pathologies", meaning that the image measure is not a Gibbs measure anymore. When such a phenomenon appears it means that conditional probabilities of the image system will acquire long-range dependencies, at least for some non-removable configurations.…”
Section: Introductionmentioning
confidence: 99%
“…As the authors of ref. 4 point out, the main (rather surprising) pathology of the above RGT is that the renormalized measure v can very well be non-Gibbsian, that is, the associated system of conditional probabilities is not compatible with any finite-norm potential. That may happen even if the starting measure p, e.g., the unique Gibbs measure of some finite-range interaction, has all the nice properties describing the one-phase region: analyticity, exponential decay of correlations, convergent cluster expansion, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. 4 one can find many examples of such pathology. Moreover, the same authors show that the typical mechanism behind the non-Gibbsianness of the measure v is the appearance of long-range order, that is, a phase transition, in the object system conditioned to some particular configurations of the image system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations